Expanding scope about factors influencing seroma formation after breast cancer surgery - Osama Eldamshety; Ahmed Lamey; Khalid Ahmed Ismail; Taha Esmail; Mohamed Tolba; Reda Ali (Journal of the Pakistan Medical Association, 2023)
Objectives: To determine the incidence of seroma formation after breast cancer surgery, and its association with common risk factors. Method: The correlational study was conducted at the General Surgery department of Kafrelsheikh University Hospital, Egypt, from March 2020 to March 2022 and comprised patients having breast cancer stage I, II or III, as per the Tumour- Node-Metastasis classification, who were scheduled to undergo modified radical mastectomy, breast conserving surgery or reconstructive surgery. Baseline, intraoperative and postoperative data was collected on a proforma. Data was analysed using SPSS 22. Results: Of the 50 female patients with mean age 45±5.20 (range: 20-70 years), 30(60%) were in the elderly group aged >45 years, while 20(40%) were aged <45years. Overall, 12(24%) cases developed seroma; 9(30%) in the elderly group. There were 24(48%) cases of modified radical mastectomy, and 8(33.3%) had seroma. Electrocautery was used for breast dissection in 30(60%) cases, and, among them, seroma developed in 10(33.3%) patients. Conclusion: Age, body weight, afflicted breast side, site, and size of breast mass were not found to be significant predictors of seroma formation following breast cancer surgery. Keywords: Seroma, Breast neoplasms, Neoadjuvant therapy, Electrocoagulation, Wound healing, Lymph nodes, Obesity.